2021
DOI: 10.1093/forestry/cpab047
|View full text |Cite
|
Sign up to set email alerts
|

The changing culture of silviculture

Abstract: Changing climates are altering the structural and functional components of forest ecosystems at an unprecedented rate. Simultaneously, we are seeing a diversification of public expectations on the broader sustainable use of forest resources beyond timber production. As a result, the science and art of silviculture needs to adapt to these changing realities. In this piece, we argue that silviculturists are gradually shifting from the application of empirically derived silvicultural scenarios to new sets of appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 79 publications
0
40
0
Order By: Relevance
“…Further evaluations of these treatments are necessary to facilitate a better understanding of the effects of thinning and prescribed burning on resistance and resilience to bark beetles and other disturbances at Pringle Falls Experimental Forest. Given climate change, this is of utmost importance [1,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further evaluations of these treatments are necessary to facilitate a better understanding of the effects of thinning and prescribed burning on resistance and resilience to bark beetles and other disturbances at Pringle Falls Experimental Forest. Given climate change, this is of utmost importance [1,48].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, Achim et al [1] argue that the science of silviculture must adapt to the reality that many forest ecosystems have been altered significantly by human interventions and climate change. As such, they question the utility of older studies to inform contemporary forest management, and highlight the need for innovative studies at appropriate scales where a range of silvicultural treatments are tested [1]. Many low to mid-elevation (e.g., <2500 m) forests in the Pacific Northwest, U.S. are fire-adapted as wildfire is an integral and predictable part of their ecological functioning [2].…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of silviculture is to improve timber productivity by applying tree improvement, site manipulation, and plant protection [63]. With agroforestry, the science of silviculture is expected to encounter issues beyond timber production [64]. Moreover, silviculture treatment on timber-based versus nontimber-based forest products provides a different result for land productivity [22].…”
Section: Existing Conditions Of Agroforestry In Indonesiamentioning
confidence: 99%
“…Similar results were found by Liang, et al [54] who showed that while disturbances may contribute to species' recruitment into new sites, they actually had a relatively small effect compared to the species' competitive abilities for establishment and growth. This underlines the fact that under a changing climate, silvicultural and harvesting practices will need to evolve to help maintain desired species in landscapes or to adapt stand composition to emerging environmental conditions [59].…”
Section: Ecosystem Processesmentioning
confidence: 99%